2021
DOI: 10.1108/irjms-08-2021-0110
|View full text |Cite
|
Sign up to set email alerts
|

From offline shopping to online shopping in Nigeria: evidence from African emerging economy

Abstract: PurposeThe study builds on studies in online shopping. Existing studies in online shopping proved that it is an attraction to shoppers. In Nigeria's emerging economy the increasing Internet penetration does not equate with intention to use online shopping because it is not really used by users for online shopping. Consumers are considering it unattractive because of serious concerns that border on product quality of online shops and poor know-how on e-tech. The study sought to explore factors that could mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
0
9
1
2
Order By: Relevance
“…The questionnaire was subjected to preliminary test using face validity and content validity through expert in the field. The moderated questionnaire by the experts were distributed through snowball sampling given that it will enable the researchers connect to individuals with experience on mHealth (Oloveze et al, 2022). The use of filter questions «have you ever used mobile health application or service or innovation» and «have you ever used any of mobicure app, hudibia app, safermom app or mobile authentication service that checkmates fake and substandard drugs» were used to screen out irrelevant responses.…”
Section: Methodology and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was subjected to preliminary test using face validity and content validity through expert in the field. The moderated questionnaire by the experts were distributed through snowball sampling given that it will enable the researchers connect to individuals with experience on mHealth (Oloveze et al, 2022). The use of filter questions «have you ever used mobile health application or service or innovation» and «have you ever used any of mobicure app, hudibia app, safermom app or mobile authentication service that checkmates fake and substandard drugs» were used to screen out irrelevant responses.…”
Section: Methodology and Research Methodsmentioning
confidence: 99%
“…Herman's single factor technique was used to check for the significance of the CMB. By adjusting all factors to single factor the value of 46.78% indicates that CMB do not have significant influence given that the threshold is 50% (Kaliniс et al, 2019;Oloveze et al, 2022). Secondly, factor analysis was conducted using principal component analysis with varimax rotation technique.…”
Section: Methodology and Research Methodsmentioning
confidence: 99%
“…For example, Daroch, Nagrath and Gupta (2020) noted that among the factors constraining consumers to shop online included fear of bank transactions, insecurities, services, experiences and trust. Similarly, in Africa, various studies (Moeti, Mokwena & Malebana, 2021;Mofokeng, 2021;Oloveze et al, 2022) have mentioned attributes that restrain consumers from shopping online. In Nigeria, Oloveze et al (2022) found that online shopping by consumers was directly affected by attitude, perceived usefulness and social influences.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Africa, various studies (Moeti, Mokwena & Malebana, 2021;Mofokeng, 2021;Oloveze et al, 2022) have mentioned attributes that restrain consumers from shopping online. In Nigeria, Oloveze et al (2022) found that online shopping by consumers was directly affected by attitude, perceived usefulness and social influences. Within Africa, the literature from Uganda and Rwanda on shopping online is scant.…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa penelitian terkait purchase intentions dalam berbelanja online telah dilakukan (Oloveze et al, 2022;Polas et al, 2022;Santo & Marques, 2022). Purchase intentions terhadap belanja online ini kemungkinan akan tetap menjadi perilaku jangka panjang.…”
unclassified